Epidemiology and results of the first line therapy for HIV-related Hodgkin lymphoma - A. M. Chekalov; M. O. Popova; I. V. Tsygankov; Yu. A. Rogacheva; N. P. Volkov; K. V. Lepik; M. V. Demchenkova; T. V. Schneider; Yu. V. Kopeikina; N. V. Medvedeva; I. S. Zyuzgin; E. S. Pavlyuchenko; et al. (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. The risk of developing Hodgkin lymphoma (HL) with HIV infection is higher than in the general population, and the course of the disease itself is more aggressive. Currently, there is no unified approach to the treatment of HIV-related HL, and data on its epidemiology in the Russian Federation are limited.The objective was to study epidemiological characteristics, the used therapeutic tactics and the results of treatment for HIV-related HL.Methods and materials. The multicenter retrospective study included 46 patients with HIV- related HL treated in 9 centers of the Russian Federation. Descriptive statistics methods were used, the analysis of overall survival (OS) and progression-free survival (PFS) was performed using the Kaplan–Meier method.Results. HIV-related HL is more often represented by an advanced stage, B-symptoms, and extranodal lesions. The ABVD regimen was used as the first-line therapy in 60 % for HIV-related HL. The overall response to therapy was 81.6 %, and the 2-year OS and PFS were 85 % and 49 %, respectively. Factors that worsened OS were CD4+˂266 cells/mcL and general somatic status ECOG≥2.